COMPETENCIES FOR MANAGING GREEN BUILDINGS: ALIGNED COMPONENTS FROM MALAYSIA’S FACILITIES MANAGEMENT SERVICE PROVIDER - Ishak, Mohd Hafizal; Ismail, Siti Nur Ayunie; Md. Yassin, Azlina; Ahmad, Nurul Afiqah (International Journal of Property Sciences (E-ISSN: 2229-8568), 2023)
The increased development of green buildings in Malaysia has necessitated the need for facility management businesses to upgrade their competencies. However, as evidenced by past studies, a shortage of competences among practitioners has emerged as an uncertainty about firms’ capacity for managing green buildings. Therefore, the purpose of the research is to acquire insight into the competency features of FM service providers in Malaysia for managing green buildings and to make recommendations for competency improvement. The qualitative approach was adopted, and interview was used to achieve the goals, the data was examined using content analysis. Based on the experiences of seven (7) managers who have managed green buildings, the five (5) core strengths of facilities management service providers in managing green buildings are sustainable procurement, operations, resource management, repair and maintenance, and environmental health. This study demonstrated common themes between facilities management and green building management competencies.